Konstruksi Kelompok Punk Gang Setan Movement terhadap Jati Diri Ke-Indonesia-an: Studi Fenomenologi Kelompok Punk Embong Kaliasin Surabaya - Ibnu Haritosanda (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
Pancasila as the ideology of the Indonesian nation should be a guideline in the life of the nation and the state for all citizens, including for groups that are often seen as opposed to the state system such as the Punk community. This research raises the Gang Satan Movement, a Punk group that understands and applies the values of Pancasila in their lives. This is interesting considering that the roots of the Punk movement in the world were born from the spirit of resistance to the state system and authority. The purpose of this study is to describe the construction of the Punk group's thinking towards the view of nationality according to the values of Pancasila, using the constructivist theory of Peter L. Berger and Thomas Luckmann as an analysis knife. This research was conducted with a qualitative approach and phenomenological methods. Data collection techniques include observation, interviews, and documentation, then analyzed using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that members of the Satanic Gang interpret Pancasila as a guide for life and the basis for behavior, and implement it in the form of solidarity, cooperation, tolerance, and love for the homeland. This implementation is shaped by three main aspects: norms, knowledge, and religion.